Identification of novel biomarkers associated with poor patient outcomes in invasive breast carcinoma - Canevari, Renata A.; Marchi, Fabio A.; Domingues, Maria A. C. [UNESP]; de Andrade, Victor Piana; Caldeira, José R. F.; Verjovski-Almeida, Sergio; Rogatto, Silvia R.; Reis, Eduardo M. (Springer Nature, 2016)
Breast carcinoma (BC) corresponds to 23 % of all cancers in women, with 1.38 million new cases and 460,000 deaths worldwide annually. Despite the significant advances in the identification of molecular markers and different modalities of treatment for primary BC, the ability to predict its metastatic behavior is still limited. The purpose of this study was to identify novel molecular markers associated with distinct clinical outcomes in a Brazilian cohort of BC patients. We generated global gene expression profiles using tumor samples from 24 patients with invasive ductal BC who were followed for at least 5 years, including a group of 15 patients with favorable outcomes and another with nine patients who developed metastasis. We identified a set of 58 differentially expressed genes (p ≤ 0.01) between the two groups. The prognostic value of this metastasis signature was corroborated by its ability to stratify independent BC patient datasets according to disease-free survival and overall survival. The upregulation of B3GNT7, PPM1D, TNKS2, PHB, and GTSE1 in patients with poor outcomes was confirmed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) in an independent sample of patients with BC (47 with good outcomes and eight that presented metastasis). The expression of BCL2-associated agonist of cell death (BAD) protein was determined in 1276 BC tissue samples by immunohistochemistry and was consistent with the reduced BAD mRNA expression levels in metastatic cases, as observed in the oligoarray data. These findings point to novel prognostic markers that can distinguish breast carcinomas with metastatic potential from those with favorable outcomes.
Keywords: Breast cancer; Gene expression; Metastasis; Prognostic gene signature; Tumor biomarkers